Appropriate Technology E-book on Mobile Learning for Mathematics Teachers - Puji Astuti; Febrian Febrian; Mirta Fera; Rindi Antika; Zhuzetta AnisaFitry; Arie Setiawan; Cyndi Wulandari; Rabiatul Mardiah; Muhammad Abdul Gani; Yodiatmana Yodiatmana (Universitas Maritim Raja Ali Haji, 2022)
Technological developments in the industrial era 4.0, which coincided with the Covid-19 Pandemic, required teachers to teach students from home. The use of technology is the right solution during the current Pandemic. This research and development aim to produce an Appropriate Technology (AT) e-book on mobile learning during a Pandemic for mathematics teachers that is valid and practical. The subjects of this study were 17 high school mathematics teachers in Lingga and Bintan districts. The research design used is the ADDIE development model, which specifically includes (1) analysis, (2) design, and (3) development. The instruments of data collection used a validation questionnaire sheet and a practicality questionnaire sheet. The data were analyzed by qualitative descriptive statistics to see the validity and practicality of the AT e-book developed. The results showed that the AT e-book was valid, as seen from the validation results of the validators, the score showed an average of 92.5% with very valid criteria. Based on the results of the practicality questionnaire, the AT e-book obtained an average score of 84.9% in the very practical criteria. This result was also confirmed by the teachers directly that the book helped them understand mobile learning easily. Therefore, it can be concluded that the AT e-book on mobile learning during the Pandemic for mathematics teachers has been categorized as valid and practical.